2014
DOI: 10.1162/jocn_a_00620
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration during Short-term Music Reading Training Enhances Both Uni- and Multisensory Cortical Processing

Abstract: The human ability to integrate the input of several sensory systems is essential for building a meaningful interpretation out of the complexity of the environment. Training studies have shown that the involvement of multiple senses during training enhances neuroplasticity, but it is not clear to what extent integration of the senses during training is required for the observed effects. This study intended to elucidate the differential contributions of uni- and multisensory elements of music reading training in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 61 publications
1
20
0
1
Order By: Relevance
“…The organization of this network indicates that musicians make greater use of the temporal sources (and auditory information accordingly). The present results closely relate to previous results reported by our group (9,10). This analysis further revealed that musicians showed significantly greater activity than nonmusicians in superior frontal, superior temporal, and lingual gyrus when confronted with incongruences.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The organization of this network indicates that musicians make greater use of the temporal sources (and auditory information accordingly). The present results closely relate to previous results reported by our group (9,10). This analysis further revealed that musicians showed significantly greater activity than nonmusicians in superior frontal, superior temporal, and lingual gyrus when confronted with incongruences.…”
Section: Discussionsupporting
confidence: 92%
“…A new dataset was created for the present study from MEG measurements that have been presented in two previous publications (9,10). In the new dataset, we included the same number of musicians and nonmusicians for whom MRI data were available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The landscape is actually quite promising in this regard since several studies now point to multisensory and unisensory gain with repeated training. These studies show that training can lead to improvement in MSI-dependent tasks such as speech-perception [53], that training can narrow the time window during which two sensory inputs are seen as “synchronous” and thus integrated [54], and that MSI networks can be engaged and enhanced in training activities where abstract stimuli are paired, such as specific sounds with abstract shapes, or musical tones with symbols [55,56]. Work in animal models also supports the notion that sensory integration abilities can be impacted through practice with training-induced multisensory enhancement noted in both behavior and activity patterns at the single cell level in the superior colliculus, in both juvenile [57] and adult cats [58].…”
Section: Discussionmentioning
confidence: 99%
“…Several electrophysiological studies have demonstrated that musicians as compared with nonmusicians exhibit different scalp topography and functional connectivity for oddball detection using audiovisual symbolic music stimuli, and this generalizes to audio–tactile stimulation . As shown in a series of MEG studies, this sensitivity to audiovisual incongruencies can also be learned via short‐term perceptual training (Table ).…”
Section: Internal Forward Models For Sensorimotor Temporal Predictionsmentioning
confidence: 99%